Está en la página 1de 5

𝒚 = 𝒙𝟑 − 𝟔𝒙𝟐 + 𝟖𝒙

2
3 2
𝑥 4 6𝑥 3 8𝑥 2
2
∫ (𝑥 − 6𝑥 + 8𝑥)𝑑𝑥 = ∫ − +
0 0 4 3 2
2 4 2 4
𝑥 3 2
𝑥
=∫ − 2𝑥 + 4𝑥 = ∫ − 2𝑥 3 + 4𝑥 2 + 𝑐
0 4 0 4

𝑥4
0 ( − 2𝑥 3 + 4𝑥 2 ) = 0
4

𝑥4 3 2
(2)4
2 − ( − 2𝑥 + 4𝑥 ) = − 2(2)3 + 4(2)2
4 4
16
= − 16 + 16 = 4 − 16 + 16 = 4𝑢2
4

4 𝑥4
A.∫2 𝑥 3 − 6𝑥 2 + 8𝑥 = − 2𝑥 3 + 4𝑥 2 + 𝑐
4

24 3 3
16
2 ( − 2(2) + 4(2) ) = − 16 + 16 = 4𝑢2
4 4

𝑥4 3 2
42
4 − ( − 2𝑥 + 4𝑥 ) = − 2(4)3 + 4(4)2
4 4
= 64 − 128 + 64 = 0
Calcular el área entre la curva y la recta siendo 𝒚 = 𝒙𝟐 −
𝟓𝒙 + 𝟔 y la recta 𝒚 = 𝟐𝒙
−(−7)√(−7)2 −4(1)(6)
a=1 𝑥1 = =6
2(1)

−(−7)−√(−7)2 −4(1)(6)
b=-7 𝑥2 = =1
2

c=6
6 𝑥3 7𝑥 2
𝑎= ∫1 ( 3 − + 6𝑥)
2

𝑥 3 7(1)2 1 7 6 1 7
1( − + 6(1)) = − + 6 = + −
3 2 3 2 1 3 2

6 6 36
( )( ) =
1 6 6
7 3 26
( )( ) =
2 3 6
1 2 2
( )( ) =
3 2 6
36 26 2 17
− + =
6 6 6 6
63 7(6)2 216 252
6−( − ( )
+6 6 )= − + 36
3 2 3 2
36 216 252
= + −
1 3 2
36 6 216
( )( ) = = 36
1 6 6
216 2 432
( )( ) = = 72
3 2 6
252 3 756
( )( ) = = −126
2 3 6
72 − 126 + 36 = −18
17 (−18)(6) − 17 125 2
−18 − = = 𝑢
6 6 6
𝒚 = 𝟔𝒙 − 𝒙𝟐 𝒚 = 𝒙𝟐 − 𝟐𝒙
√𝑏 2 −4𝑎𝑐
a=2 𝑏± 2𝑎

√(8)2 −4(2)(0) 8+8


b=8 𝑥1 = −(8) + = =4
2(2) 4

c=0
√(8)2 4(2)(0) 8−8
𝑥2 = −(−8) − = =0
2(2) 4

4
𝑎 = ∫ [(6𝑥 − 𝑥 2 ) − (𝑥 2 − 2𝑥 )] 𝑑𝑥
0
4
2
2𝑥 3 8𝑥 2 2𝑥 3
∫ 2𝑥 − 8𝑥 = − = − 4𝑥 2
0 3 2 3
2𝑥 3 2(0)3
0( − 4𝑥 2 ) = − 4(0)2 = 0
3 3

2𝑥 3 2
2(4)3 2
128 64 2
4−( − 4𝑥 ) = − 4(4) = − 64 = 𝑢
3 3 3 3
𝑦 = 𝑥2 + 2

1
∫ (𝑥 2 + 2)
2

𝑥3 (1)3 1 (2)(3) 1 7
1 ( + 2𝑥) = + 2(1) = + 2 = + =
3 3 3 3 3 3

𝑥3 (2)3 8 (4)(3) 8 20
2 − ( + 2𝑥) = + 2(2) = + 4 = + =
3 3 3 3 3 3
20 7 13
− =
3 3 3

𝒚 = −𝒙 − 𝟏
1
𝑥2
∫ (−𝑥 − 1) = − − 𝑥
2 2
𝑥2 12 1
1 (− − 𝑥) = − − 1 =
2 2 2

𝑥2 22 4
2 − (− − 𝑥) = − − (−2) = − + 2 = 0
2 2 2
13 1 26 + 3 29 2
𝑎= + = = 𝑢
3 2 6 6